2019
DOI: 10.21608/ejabf.2019.53599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α-Chlorohydrin water-bait on the fertility of captive males of the Egyptian fruit-bat (Rousettus aegyptiacus) and the proper time for controlling its free-ranging populations in Egypt

Abstract: Water-bait Egyptian fruit-bat Rousettus aegyptiacus α-chlorohydrin antifertility controlThe Egyptian fruit-bat (Rousettus aegyptiacus) is a serious vertebrate pest that lives in riverine and agricultural habitats of the Nile Delta and Valley of Egypt. The present work evaluates the acceptability and effect of a water bait of α-chlorohydrin (ACH), which is a well-known species-specific male chemosterilant, on the fertility of males of this bat species. A dose of 85.7mg/kg consumed by captive males for four cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…These results indicated that both fungal extracts had highly destructive effects on the count and motility of epididymal sperm compared to the control rats. The results were consistent with those of other researchers, who reported that sperm count and motility were vital factors and that any changes in sperm count and motility could be used as an indicator for measuring normal fertility by measuring sperm fertilizing capacity in animals (Mahmoud et al 2018;Taha and Soliman 2019). The reduction in the count and motility of epididymal sperm was attributed to the reduced supply of testosterone in the epididymis (Gong and Han 2006).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These results indicated that both fungal extracts had highly destructive effects on the count and motility of epididymal sperm compared to the control rats. The results were consistent with those of other researchers, who reported that sperm count and motility were vital factors and that any changes in sperm count and motility could be used as an indicator for measuring normal fertility by measuring sperm fertilizing capacity in animals (Mahmoud et al 2018;Taha and Soliman 2019). The reduction in the count and motility of epididymal sperm was attributed to the reduced supply of testosterone in the epididymis (Gong and Han 2006).…”
Section: Discussionsupporting
confidence: 91%
“…The activity of the ATPase enzyme in the spermatozoa cell membrane could be affected by alkaloid compounds and the distributing balance of sodium and potassium ions (Hidayati et al 2018). The morphology of sperm is a vital parameter that reflects their normality and maturity and is directly correlated with male fertility (Memon et al 1986;Taha and Soliman 2019). Head and mid-piece sperm abnormalities were identified as mainly prime spermatogenesis defects (Schumacher and Moll 2011;Taha and Soliman 2019) and were valuable indicators of testicular degeneration (Bloom 1950;Taha and Soliman 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations